2016
DOI: 10.5901/mjss.2016.v7n2p445
|View full text |Cite
|
Sign up to set email alerts
|

A Pragmatic Study of the Recognition and Interpretation of Verbal Irony by Malaysian ESL Learners

Abstract: Verbal irony is understood to be a strategy that uses incongruity between reality and expectation. Since it intends to Kumon-Nakamura, et al. (1995) and Utsumi's (2000) implicit display theory are adopted. To investigate the interpretation of ironic utterances, Kreuz and Link (2002) canonical/non-canonical types of irony are identified. These types, in turn, are categorized according to the pragmatic strategies adopted form Gibbs (2000)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…As part of this study, we also identified the most cited pragmatics documents. These included the discussion of different topic of which are qualitative content analysis in nursing research [ 74 ], pedagogy of multiliteracies [ 60 ], measuring recognition [ 130 ] and the pragmatics of model-driven developments [ 79 ]. Such studies provide measures to achieve trustworthiness in qualitative content analysis including credibility, dependability, and transferability.…”
Section: Discussionmentioning
confidence: 99%
“…As part of this study, we also identified the most cited pragmatics documents. These included the discussion of different topic of which are qualitative content analysis in nursing research [ 74 ], pedagogy of multiliteracies [ 60 ], measuring recognition [ 130 ] and the pragmatics of model-driven developments [ 79 ]. Such studies provide measures to achieve trustworthiness in qualitative content analysis including credibility, dependability, and transferability.…”
Section: Discussionmentioning
confidence: 99%
“…The importance of context in the ability of ESL speakers to disambiguate the true intent of English sarcasm has been supported by several studies (Filippova, 2014;Peters et al, 2016;Salman, 2016). Peters et al (2016) suggest that ESL speakers rely more heavily on context than prosody when identifying sarcasm.…”
mentioning
confidence: 95%
“…Although early research suggested that sarcasm is absent from some languages (Haiman, 1998;Kreuz et al, 1998), more recent research suggests that it is found in most languages, but includes cultural variations in the frequency of the production of sarcasm as well as its function (Ghezzi & Molinelli, 2019;Lee & Katz, 1998;Rockwell, 2006;Toplak & Katz, 2000). Salman (2016) found that Malaysian ESL participants generally had difficulty detecting sarcasm when it was used in an evaluative, humorous, or mocking manner. Likewise, Filippova (2014) found that ESL participants from the Czech Republic were better than NE speakers at identifying ironic sarcastic criticism, whereas the NE speakers were better at identifying ironic praise.…”
mentioning
confidence: 99%